ANALYSIS OF HEALTH STUDENTS' PROFICIENCY IN MEDICAL ENGLISH TERMINOLOGY THROUGH IMAGES AND TEXTS AT STIKES NGUDIA HUSADA MADURA - Irianto, Dhaniel Prasetyo; Nurniati, Emi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyse the proficiency of health students in mastering medical English terminology through the use of images and texts at STIKES Ngudia Husada Madura. The research employs a qualitative descriptive design, with the population consisting of health students who have undertaken a medical English course. The sample was purposively selected, involving students actively using images and texts in their learning. Research instruments included a medical English terminology test and a questionnaire or interviews about students' experiences with these learning media. Data were collected through administering tests, completing questionnaires, and conducting interviews, and were subsequently analysed using qualitative data analysis methods. The findings indicate that the use of images and texts significantly enhances students' understanding and proficiency in medical English terminology. The average test scores were higher among students exposed to image and text-based learning compared to those using text alone. Qualitative analysis revealed that images assist students in associating medical terms with concrete visualisations, while texts provide the necessary linguistic context for deeper understanding. Additionally, lecturer support and the quality of learning materials were crucial to the success of this method. The implications of this study include recommendations for integrating the use of images and texts into the medical English curriculum at health education institutions. This innovative teaching method can improve students' competence in understanding and using medical terminology and motivate them to be more active in their learning process. The study also identifies several limitations, such as the generalisability of results and the measurement methods used, and suggests further research with a broader scope and diverse methodological approaches to confirm and extend these findings.